2022
DOI: 10.2460/javma.22.05.0192
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic structures of the canine middle ear visible during endoscopic examination through a ventral or lateral approach

Abstract: OBJECTIVE To describe the anatomic structures of the canine middle ear visible during endoscopic examination through ventral and lateral surgical approaches. SAMPLE 5 cadaveric canine heads representing 4 breeds. PROCEDURES A descriptive study was performed. For each head, a lateral approach was performed on one side and a ventral approach was performed on the opposite side. Images were obtained with a 2.7-mm, 30° telescope. RESULTS Captured images were reviewed, and anatomic structures visualized throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the feline cadavers studied, the addition of an endoscope to the traditional TECA-LBO approach was observed to be technically simple and was able to be facilitated through the lateral bulla osteotomy site without the need for an additional or expanded approach. A previous study in canine cadavers resulted in the successful visualization of 14 notable structures of the middle ear via lateral endoscopic visualization using a 2.7 mm 30° scope; 9 in the current study, only 12 structures were able to be directly observed via this approach. Structures unable to be identified in the cat compared with the dog included tympanic bone spicules and the tympanic plexus.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the feline cadavers studied, the addition of an endoscope to the traditional TECA-LBO approach was observed to be technically simple and was able to be facilitated through the lateral bulla osteotomy site without the need for an additional or expanded approach. A previous study in canine cadavers resulted in the successful visualization of 14 notable structures of the middle ear via lateral endoscopic visualization using a 2.7 mm 30° scope; 9 in the current study, only 12 structures were able to be directly observed via this approach. Structures unable to be identified in the cat compared with the dog included tympanic bone spicules and the tympanic plexus.…”
Section: Discussionmentioning
confidence: 60%
“…In human otolaryngology, endoscopy has gained popularity in the diagnostic assessment of the middle ear, as well as visualization during surgery, and is acknowledged as an effective means of identifying ear anatomy and adequately illuminating the middle ear during surgical procedures. 7 , 8 A recent veterinary study has illustrated that an endoscope can be used to effectively identify the structures of the canine middle ear after lateral and ventral bulla osteotomy, 9 but so far, no attempts have been documented to assess endoscopic evaluation of middle ear structures in cats. In addition, there is no existing literature evaluating the use of scope assistance for increasing effective hypotympanum entry during feline TECA-LBO.…”
Section: Introductionmentioning
confidence: 99%